(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2023)
Background. The practical use of 3-hetarylcoumarin derivatives relates to their valuable spectral and biological characteristics, which are determined by the nature of the substituents in the basic structure. Earlier, on the base of 2-amino-3,3-dichloroacrylonitrile (ADAN), the method for the synthesis of new oxazole derivatives was developed by us, and the possibility of 5-amino-4-cyanooxazol-2-yl)acetate’s obtaining by its following cyclization into the coumarin cycle was shown. In this study, the synthesis of new 3-(5-amino-4-cyanoxazol-2-yl)coumarins, as well as determination of their ability to inhibit the growth of cancer cells, were represented. The objects of investigation are heterocyclization as a method for 3-(5-amino-4-cyanoxazol-2-yl)coumarins obtaining, as well as spectral and biological characteristics of the synthesized substances. Methods. Organic synthesis of new derivatives of (5-amino-4-cyanoxazol-2-yl)acetic acid and 3-(5-amino-4-cyanoxazol-2-yl)coumarin; characterization of the synthesized substances using 1Н, 13С NMR spectroscopy and chromatography-mass spectrometry; single-dose tests of anticancer activity of three derivatives on 60 cancer cell lines. Results. Based on ADAN, a number of new derivatives of 3-(5-amino-4-cyanoxazol-2-yl)coumarin were synthesized in different ways: 1) formation of (5-amino-4-cyanoxazol-2-yl)acetic acid derivatives and their subsequent cyclization with salicylic aldehydes into coumarins; 2) acylation of the ADAN amino group with coumarin-3-carboxylic acid chloroanhydride and subsequent formation of an oxazole substituent at the 3-position of coumarin under the action of amines. It has been established that the anticancer activity of 3-(5-amino-4-cyanoxazol-2-yl)coumarins is generally very low, and they are able to slightly slow down the growth of only certain lines. Conclusions. It is shown that for the synthesis of 3-(5-amino-4-cyanoxazol-2-yl)coumarins derivatives (in particular, compounds with active functional groups – hydroxyl, ester) two alternative synthetic schemes can be successfully applied, and due to the convenience of the techniques, it is possible to easily achieve a large variety of such derivatives. The low anticancer activity of some synthesized derivatives is consistent with the low toxicity inherent in the majority of 3-hetarylcoumarins.